A sequence of positive reals is defined as below:
a 0 = 1 , a n + 2 = 2 a n − a n + 1 ∀ n ∈ N 0
Find the sum of all values of a 2 0 1 7 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This question doesn't seem to have enough information since we don't even know what a 1 is! However, we will soon find that we have all the information we need. Remember, the sequence is defined for positive reals. For now, let a 1 = x . We have
a 0 = 1 a 1 = x a 2 = 2 − x a 3 = 3 x − 2 a 4 = 6 − 5 x a 5 = 1 1 x − 1 0 ⟹ x > 0 ⟹ x < 2 ⟹ x > 3 2 ⟹ x < 5 6 ⟹ x > 1 1 1 0
It seems that as the terms progress further, a 1 is being squeezed between two fractions towards 1. Let's try and prove that a 1 = 1 .
Firstly, let us set x = 0 so we get a new sequence b 0 = 1 , b 1 = 0 , b 2 = 2 , b 3 = − 2 , b 4 = 6 , b 5 = − 1 0 , … . Notice that from b 2 onwards, the sequence alternates in sign, with ∣ b n + 2 ∣ > ∣ b n ∣ . Let's try and prove this conjecture via induction.
Let b 2 n = p , b 2 n + 1 = − q , where n , p , q are positive integers. If n = 1 , we have p = q = 2 , which alternate in sign, as per the induction hypothesis.
If n = k , we have b 2 k + 2 = 2 r − s > r > 0 , and b 2 k + 3 = − ( 2 r + 3 s ) < 0 , with ∣ − ( 2 r + 3 s ) ∣ > s
From this, we get b 2 k + 2 > b 2 k > 0 and b 2 k + 3 < b 2 k + 1 < 0 , so our conjecture must be true by induction.
Notice also that the difference between the absolute value of the coefficients of x and the absolute value of the constant term in each term of the recurrence is 1. We will now show this to be true. If we substitute x = 1 , we get a n = 1 ∀ n ∈ N 0 . Thus, our observation must be true. Therefore,
a 2 n = b 2 n − ( b 2 n − 1 ) x a 2 n + 1 = b 2 n + 1 − ( b 2 n + 1 − 1 ) x ⟹ x < b 2 n − 1 b 2 n ⟹ x > b 2 n + 1 − 1 b 2 n + 1
Since both ∣ b 2 n ∣ and ∣ b 2 n + 1 ∣ are strictly increasing with n , the limit as n tends to ∞ of both b 2 n − 1 b 2 n and b 2 n + 1 − 1 b 2 n + 1 is 1.
Therefore, by Squeeze Theorem, we must have x = 1 , so a n = 1 ∀ n ∈ N 0 . Thus, the sum of all values of a 2 0 1 7 is 1.
It is slightly easier to use the theory of linear recurrence relations to conclude that a i = A ( − 2 ) i + B ( 1 ) i . Then, if A = 0 , we would have some a i < 0 . Thus A = 0 so a i is the constant sequence.
Problem Loading...
Note Loading...
Set Loading...
From the theory of linear recurrence relations , since the characteristic equation is m 2 + m − 2 = ( m + 2 ) ( m − 1 ) , hence the recurrence relation has the form a i = A ( − 2 ) i + B ( 1 ) i .
If A = 0 , then we eventually would have a large enough i such that A ( − 2 ) i < − ∣ B ∣ , which would make a i = A ( − 2 ) i + B < 0 . Hence, we have A = 0 and so a i = B is the constant sequence.
Thus, a 2 0 1 7 = a 0 = 1 .